Impact of economic policy in renovation on Vietnam's rural and agriculture : - Le, Canh Dung (Kangwon National University, Korea, 1998)
This research generalizes effects of land policy that has played a crucial role in improving Vietnamese agriculture. Agricutural production just increases under the mechanism of household autonomy, in which the long-term land-use right is given to farmers. As the evidence, it had led the country from a net food importer to a second rice exporter in the world recently. Upon the agricultural promotion in general, the change of rural and household status is the argument of this research presented in the late past. A case study was conducted in the flooding area, the formerly most unfavorable one of the Mekong Delta, Vietnam. This was carried out with 123 households, consisting of 95 farm households and 28 non-farm households, in order to compare the economic situation of the region, as well as that of household during the period of reform policy applied, from 1988 to 1998